Kepemimpinan Kepala Sekolah Dalam Meningkatkan Profesionalisme Guru di SMP Negeri 1 Hamparan Perak Kabupaten Deli Serdang - Natalia, Pesta (Jurnal Manajemen Pendidikan Dasar, Menengah dan Tinggi [JMP-DMT], 2024)
The purpose of this study was to determine the Principal's Strategy in improving teacher professionalism at SMP Negeri 1 Hamparan Perak, Deli Serdang Regency, the Principal's leadership role that can improve teacher professionalism at SMP Negeri 1 Hamparan Perak and what obstacles the Principal faces in improving teacher professionalism at SMP Negeri 1 Hamparan Perak. This research method is qualitative research with a description approach. Data collection is done by documentation, observation and interviews. Data analysis techniques use data reduction, data presentation and conclusions. The results of the research and conclusions are (1). Good principal leadership will produce a good school community performance which will certainly affect the quality of education. (2). The role of the principal of SMPN 1 Hamparan Perak to improve teacher professionalism is very large. (3). The obstacles that occur in the leadership of the principal of SMPN 1 Hamparan Perak to improve teacher professionalism are the lack of time for the principal to monitor activities, then teachers who do not understand the syntax of innovative learning models and learning facilities that are still incomplete.